If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(u + 6) = -6u + -42 Reorder the terms: -9(6 + u) = -6u + -42 (6 * -9 + u * -9) = -6u + -42 (-54 + -9u) = -6u + -42 Reorder the terms: -54 + -9u = -42 + -6u Solving -54 + -9u = -42 + -6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '6u' to each side of the equation. -54 + -9u + 6u = -42 + -6u + 6u Combine like terms: -9u + 6u = -3u -54 + -3u = -42 + -6u + 6u Combine like terms: -6u + 6u = 0 -54 + -3u = -42 + 0 -54 + -3u = -42 Add '54' to each side of the equation. -54 + 54 + -3u = -42 + 54 Combine like terms: -54 + 54 = 0 0 + -3u = -42 + 54 -3u = -42 + 54 Combine like terms: -42 + 54 = 12 -3u = 12 Divide each side by '-3'. u = -4 Simplifying u = -4
| 2x*x-6x+3=0 | | 5(2x+6)=4(2x+5)+3x | | 7x+7=3x+15 | | -6w+3(w-3)=-12 | | -7p-12=-4p+3[-4-p] | | 29=4u-11 | | x/5-11 | | 5x*x+5x=0 | | -22=2[x-10] | | r+11+8r=11r | | 5x-8=30x+2 | | x=-3(y+1) | | 2v+12=-7(v-3) | | 4x^2+8=136 | | abs(8-2x)=x+5 | | 5[x-4]=-60 | | -21-8a=-1+6[4-5a] | | 2x^2-6x+7=y | | 6x^2-6=594 | | 16-4y=0 | | h^2+14=9h | | 14y-3x=90 | | -35=-5u+2(u-4) | | 0.5(4x-10)+5=x-10 | | -56=7[x-3] | | X^2/2=50 | | -3.876+2x=-9.34 | | 3x+48=6x-9 | | -6[k+1]=-3-[6k+3] | | 5y-6=7y-5 | | 13.71+0.12h=14.21-0.14h | | 3.876+2x=-9.34 |